Optimization of 4D polymer printing within a massively parallel flow-through photochemical microreactor. Issue 19 (8th April 2016) - Liu, Xiaoming; Zheng, Yeting; Peurifoy, Samuel R.; Kothari, Ezan A.; Braunschweig, Adam B.
Abstract : Brush polymer patterns, where the position ( x, y ), height ( z ), and chemical composition of each feature in an array were controlled independently, were prepared by combining massively parallel tip-based photolithography, microfluidics, and photochemical radical polymerizations. Abstract : 4D polymer micropatterning – where the position ( x, y ), height ( z ), and monomer composition of each feature in a brush polymer array is controlled with sub-1 micrometer precision – is achieved by combining a mobile, massively parallel flow-through photoreactor with thiol-acrylate photoinitiated brush polymerizations. Polymers are grown off the surface by introducing monomer, photoinitiator, and solvent into the microfluidic reaction chamber, and using light reflected onto the back of elastomeric massively-parallel tip arrays to localize reactions on the surface. The ability to form fluorescent patterns by the thiol-acrylate brush polymerization from a thiol-terminated glass surface was explored with respect to reaction time, light intensity, monomer : photoinitiator ratio, and compression between the elastomeric pyramidal tips and the substrate, resulting in feature diameters as small as 480 nm, and polymer heights approaching 500 nm. Subsequently, optimized printing conditions were used to create patterns containing multiple inks by introducing new monomers via the flow-through microfluidics. Because of the wide-functional group tolerance of the thiol-acrylate reaction, surfaces enabled by this printing strategy could possess emergent optoelectronic, biological, or mechanical properties that arise from synergies between molecular composition and nanoscale geometries.